Impacts of Land Certification on Tenure Security: Investment, and Land Market Participation : Evidence from Ethiopia - Deininger, Klaus; Ali, Daniel Ayalew; Alemu, Tekie (2012)
While early attempts at land titling in Africa were often unsuccessful, factors such as new legislation, low-cost methods, and increasing demand for land have generated renewed interest. A four-period panel allows use of a pipeline and difference-indifferences approach to assess impacts of land registration in Ethiopia. We find that the program increased tenure security, land-related investment, and rental market participation and yielded benefits significantly above the cost of implementation.